Ethnopharmacology of medicinal plants used by the Tenggerese community in Bromo Tengger Semeru National Park, Indonesia - WEKA SIDHA BHAGAWAN; WIWIED EKASARI; MANGESTUTI AGIL (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Bhagawan WS, Ekasari W, Agil M. 2023. Ethnopharmacology of medicinal plants used by the Tenggerese community in Bromo Tengger Semeru National Park, Indonesia. Biodiversitas 24: 5464-5477. Bromo Tengger Semeru National Park is a repository of biodiversity with profound cultural significance. The Tenggerese community residing within the park possesses rich ethnopharmacological knowledge, using medicinal plants for various ailments. This study aims to comprehensively explore the medicinal plant diversity, traditional uses, and potential pharmacological activities among the Tenggerese people. Ethnopharmacological data was gathered through interviews with informants in seven Tenggerese villages. Ethnopharmacological indices like Species Use Value (SUV) and Fidelity Level (FL) were calculated to identify the most important medicinal plants. Phytochemical analysis of selected medicinal plants was conducted using UPLC-QTOF-MS/MS, and its pharmacological potential was assessed through antibacterial tests. A total of 124 medicinal plant species from 54 families were documented. The Tenggerese community utilizes plants to treat diverse diseases, with reproductive healthcare being prominently featured. Elaeocarpus longifolius emerged as a key species with high SUV and FL values. Phytochemical analysis identified 25 compounds, including major and minor compounds, already known for their pharmacological activities elsewhere. Elaeocarpus longifolius extract showed inhibitor activity against both gram-positive and gram-negative bacteria. The findings contribute to bridging traditional knowledge and modern scientific research, offering potential avenues for the development of drug candidates from indigenous medicinal plants.